1999
DOI: 10.1128/mcb.19.6.4167
|View full text |Cite
|
Sign up to set email alerts
|

GCD14p, a Repressor ofGCN4Translation, Cooperates with Gcd10p and Lhp1p in the Maturation of Initiator Methionyl-tRNA inSaccharomyces cerevisiae

Abstract: Gcd10p and Gcd14p were first identified genetically as repressors of GCN4 mRNA translation in Saccharomyces cerevisiae. Recent findings indicate that Gcd10p and Gcd14p reside in a nuclear complex required for the presence of 1-methyladenosine in tRNAs. Here we show that Gcd14p is an essential protein with predicted binding motifs for S-adenosylmethionine, consistent with a direct function in tRNA methylation. Two different gcd14 mutants exhibit defects in cell growth and accumulate high levels of initiator met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 72 publications
6
78
0
Order By: Relevance
“…We found that reduced synthesis of G nucleotides in gua1-G388D cells impairs the processing of pre-tRNA i Met and precursors of certain elongator tRNA species (Figure 7). The predicted reduction in SAM biosynthesis and hypomethylation of pre-tRNAs might impede their proper folding and processing, as occurs in gcd10 and gcd14 mutants defective in methylation of m1A 58 (Anderson et al 1998;Calvo et al 1999). It is also interesting to note that Ran-dependent nucleocytoplasmic transport is dependent on both GTP-and GDPbound forms of the Ran GTPase, and that defects in tRNA maturation have been observed in nucleoporin mutants (Gorlich et al 1996;Sharma et al 1996;Izaurralde et al 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that reduced synthesis of G nucleotides in gua1-G388D cells impairs the processing of pre-tRNA i Met and precursors of certain elongator tRNA species (Figure 7). The predicted reduction in SAM biosynthesis and hypomethylation of pre-tRNAs might impede their proper folding and processing, as occurs in gcd10 and gcd14 mutants defective in methylation of m1A 58 (Anderson et al 1998;Calvo et al 1999). It is also interesting to note that Ran-dependent nucleocytoplasmic transport is dependent on both GTP-and GDPbound forms of the Ran GTPase, and that defects in tRNA maturation have been observed in nucleoporin mutants (Gorlich et al 1996;Sharma et al 1996;Izaurralde et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in GCD genes (Harashima and Hinnebusch 1986;Niederberger et al 1986;Cuesta et al 1998;Calvo et al 1999) or in the recently identified GCD17/ RPL33A gene (Martin-Marcos et al 2007), lead to constitutive derepression of GCN4 translation independent of the positive regulators Gcn2 and Gcn3 and of amino acid availability. In this article, we report the identification of a gua1-G388D mutation in a GMP synthase that provokes constitutive derepression of GCN4 Figure 1.-Pathways of purine nucleotide biosynthesis in Saccharomyces cerevisiae.…”
mentioning
confidence: 99%
“…We infer that this reflects association of Lhp1p with a pre-SCR1 species elongated at its 3Ј end. Previous work (25,26) has indicated that Lhp1p binds and may function to stabilize pre-RPR1. We observe an interaction with the adjacent intergenic region directly downstream of RPR1 and believe this to be an association with 3Ј extended pre-RPR1.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, tRNA Ser (CGA), previously shown to be associated with Lhp1p (5), is in the top 100. Of the 11 other tRNAs previously suggested to be associated with Lhp1p, based on the observation that aberrant pre-tRNA processing was observed in strains deleted for LHP1 (5,25), 10 are in the top 100, and one was undetected. Interestingly, tRNA Leu (CAA), which was not shown to require LHP1 for processing (5), is Lhp1p-associated.…”
Section: Resultsmentioning
confidence: 99%
“…Gcd10p/Gcd14p catalyzes formation of m 1 A 58 in a number of tRNAs (Anderson et al 1998(Anderson et al , 2000, and is essential for modification of tRNA i Met (Calvo et al 1999), and Tad2p/Tad3p catalyzes formation of I 34 in the wobble position of the anticodon of tRNA Ala (Gerber and Keller 1999), and is presumably essential for proper decoding during translation. Strains lacking each of three other modification enzymes are viable, but have distinct growth defects (Lecointe et al 1998;Bjork et al 2001;Pintard et al 2002), whereas lack of most other modification proteins has only subtle growth defects.…”
Section: Discussionmentioning
confidence: 99%